The effect of financial liberalization towards financial stability of Islamic banks in Malaysia / Nur Afizah Muhamad Arifin ...[et al.] - Muhamad Arifin, Nur Afizah; Mohd Arifin, Noraini; Ramly, Zulkufly; Hashim, Maryam Jameelah; Abdul Aziz, Nor Farradila; Kamaralzaman, Surianor (Faculty of Business and Management UiTM Shah Alam, 2020)
Zulkufly Ra Financial liberalization will affect the stability of the financial system due to excessive risk. Liberalization effort in Islamic banks players raises the issues of the ability of how Islamic banks can survive in the financial liberalization regime. Financial liberalization induced competition and thus impact on financial stability due to excessive risk taking. Malaysia is operating in dual financial system, the effect of mediating roles of competition and interest rate between financial liberalization is expected to be vary at some extend due to shariah constraint. This paper aims to analyze the effect financial liberalization and financial stability. Structural equation model - Partial least square (PLS-SEM) is used to analyze the research model with a comprehensive data set covering the Islamic banks over 1994 -2017. The empirical results denote a significant negative impact of financial liberalization on Islamic banks' financial stability in Malaysia. Lastly, it can be concluded that this study has an implication for policymakers and the banking industry